PERENCANAAN LINGKUNGAN DAN BANGUNAN BERKELANJUTAN DI INDONESIA: TINJAUAN DARI ASPEK PERATURAN PERUNDANG-UNDANGAN - Muhammad Syarif Hidayat (TATALOKA, 2017)
Definitions of green buildings, in essence it should be environmentally friendly and sustainable ranging from planning, implementation to operation of the building. In the implementation of the legislation is needed to ensure its implementation. Candy MOE issued a regulation on the criteria and certification of environmentally friendly building where the content has some similarities with the green building parameters issued by GBCI. Parameter issued by GBCI is Appropriate Land, Energy Efficiency and Refrigerants, Water Conservation, Resource and Material Cycle, Quality and Comfort Air, and the Built Environment Management. This research question is whether there are other laws that support the concept of building a 'green'. The method used is descriptive review the regulations of the aspects of green building. The results showed that there are many laws and regulations in Indonesia has not accommodate green building design criteria. This could mean there are no rules or regulations already exist, but still expressed in general.